SATB1 ensures appropriate transcriptional programs within naïve CD8+ T cells. Issue 8 (13th July 2022) - Nüssing, Simone; Miosge, Lisa A; Lee, Kah; Olshansky, Moshe; Barugahare, Adele; Roots, Carla M; Sontani, Yovina; Day, E Bridie; Koutsakos, Marios; Kedzierska, Katherine; Goodnow, Christopher C; Russ, Brendan E; et al.
Abstract: Special AT‐binding protein 1 (SATB1) is a chromatin‐binding protein that has been shown to be a key regulator of T‐cell development and CD4 + T‐cell fate decisions and function. The underlying function for SATB1 in peripheral CD8 + T‐cell differentiation processes is largely unknown. To address this, we examined SATB1‐binding patterns in naïve and effector CD8 + T cells demonstrating that SATB1 binds to noncoding regulatory elements linked to T‐cell lineage–specific gene programs, particularly in naïve CD8 + T cells. We then assessed SATB1 function using N ‐ethyl‐ N ‐nitrosourea‐mutant mice that exhibit a point mutation in the SATB1 DNA‐binding domain (termed Satb1 m1Anu/m1Anu ). Satb1 m1Anu/m1Anu mice exhibit diminished SATB1‐binding, naïve, Satb1 m1Anu/m1Anu CD8 + T cells exhibiting transcriptional and phenotypic characteristics reminiscent of effector T cells. Upon activation, the transcriptional signatures of Satb1 m1Anu/m1Anu and wild‐type effector CD8 + T cells converged. While there were no overt differences, primary respiratory infection of Satb1 m1Anu/m1Anu mice with influenza A virus (IAV) resulted in a decreased proportion and number of IAV‐specific CD8 + effector T cells recruited to the infected lung when compared with wild‐type mice. Together, these data suggest that SATB1 has a major role in an appropriate transcriptional state within naïve CD8 + T cells and ensures appropriate CD8 + T‐cell effector gene expression upon activation. Abstract : We examine the role of special AT‐binding protein 1 (SATB1), a chromatin‐binding protein, in the establishment of naïve and virus‐specific CD8 + T cells.